The translation of entrepreneurial intention into start-up behaviour: The moderating role of regional social capital. (August 2019) - Weiss, Jan; Anisimova, Tatiana; Shirokova, Galina
This article examines the moderating role of regional social capital in the intention–behaviour link in entrepreneurship. We investigate to what extent the regional social capital context in which aspiring entrepreneurs are embedded strengthens or weakens the translation of individual entrepreneurial intentions into new venture creation activities. Our results suggest that the intention–behaviour link is weakened by cognitive regional social capital in the form of regional hierarchy values and strengthened by structural regional capital in the form of regional cultural diversity and regional breadth of associational activity, as well as by relational regional social capital in the form of high levels of regional generalised trust. Our findings suggest that to support new venture creation activity, there is a need to grow regional social capital via the enhancement of social trust, associational activities and regional cultural diversity – and at the same time decrease hierarchical social structures within regions.